Cobalt ion-enhanced photochemical vapor generation in a mixed acid medium for sensitive detection of tellurium(iv) by atomic fluorescence spectrometry. Issue 7 (9th June 2020) - Zeng, Wen; Hu, Jing; Chen, Hanjiao; Zou, Zhirong; Hou, Xiandeng; Jiang, Xiaoming
Abstract : Cobalt ion-assisted enhancement of photochemical vapor generation in a mixed acid medium was used for sensitive determination of tellurium(iv ) by atomic fluorescence spectrometry. Abstract : A method of cobalt ion assisted enhancement of photochemical vapor generation-atomic fluorescence spectrometry (PVG-AFS) was proposed for sensitive determination of ultratrace tellurium(iv ). With a mixture of 5% (v/v) formic acid and 20% (v/v) acetic acid as the reaction medium, more than 13-fold improvement in AFS intensity for Te(iv ) was achieved simply by adding 1 mg L −1 Co 2+ as a homogeneous catalyst. A possible reaction mechanism was proposed with the characterization results of GC-MS and electron paramagnetic resonance (EPR). Under optimal conditions, the limit of detection (LOD) for Te(iv ) was 0.06 μg L −1, with a relative standard deviation (RSD) of 1.3% (10 μg L −1 Te, 7 times). The accuracy and utility of this methodology were validated by analysis of real water samples, with satisfactory recoveries of 91–108%.